PENGARUH KEGIATAN ROCK PAINTING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA 5–6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL TEMBESI - Lilis Karlina; Haryanto Haryanto; Asih Nur Ismiatun (STKIP Subang, 2026)
This study was motivated by the low development of fine motor skills among children aged 5–6 years at TK Aisyiyah Bustanul Athfal Muara Tembesi. The problems identified include children’s difficulties in cutting according to patterns, pasting accurately, writing, and coordinating hand movements. This study aims to determine the effect of rock painting activities on the fine motor skills development of early childhood. The research employed a quantitative approach using a pre-experimental design with a one group pretest-posttest design. The sample consisted of 19 children in group B. Data were collected using an observation sheet that had been tested for validity. Data analysis techniques included normality test, homogeneity test, and hypothesis testing using paired sample t-test. The results showed a significant effect of rock painting activities on children's fine motor skills, indicated by improvements in hand-eye coordination, finger control, and precision in coloring and drawing activities. In conclusion, rock painting activities are effective as an innovative and enjoyable learning method to improve fine motor skills in early childhood.